2022
DOI: 10.1186/s12915-021-01184-0
|View full text |Cite
|
Sign up to set email alerts
|

Conventional laboratory housing increases morbidity and mortality in research rodents: results of a meta-analysis

Abstract: Background Over 120 million mice and rats are used annually in research, conventionally housed in shoebox-sized cages that restrict natural behaviours (e.g. nesting and burrowing). This can reduce physical fitness, impair thermoregulation and reduce welfare (e.g. inducing abnormal stereotypic behaviours). In humans, chronic stress has biological costs, increasing disease risks and potentially shortening life. Using a pre-registered protocol (https://atrium.lib.uoguelph.ca/xmlui/handle/10214/179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 167 publications
0
39
0
4
Order By: Relevance
“…We suggest that several of these more frequently endorsed elements (i.e., social housing, nesting material, shelters, foraging opportunities) are now sufficiently established that they should be regarded as basic to good rodent housing conditions rather than “enriched”, or that systems that fail to include these features be considered impoverished. Others have suggested that conventional housing should be more formally recognised as a stressful laboratory procedure [ 21 ]. Such framing may help motivate change in laboratories that until now have been unable or unwilling to include these features.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We suggest that several of these more frequently endorsed elements (i.e., social housing, nesting material, shelters, foraging opportunities) are now sufficiently established that they should be regarded as basic to good rodent housing conditions rather than “enriched”, or that systems that fail to include these features be considered impoverished. Others have suggested that conventional housing should be more formally recognised as a stressful laboratory procedure [ 21 ]. Such framing may help motivate change in laboratories that until now have been unable or unwilling to include these features.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta-analysis of 281 rodent enrichment studies concluded that complex housing does not make results any more variable in comparison to conventional laboratory housing [ 46 ]. Another recent systematic review of rodents induced with stress-sensitive diseases found no effect of housing conditions on variation [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations